The fictionalization of independence in two novels written during the first centennial celebrations - Pollarolo, Giovanna (2021)
As part of the celebrations of 1921-1924, the government of President Leguía called the Contest for the Centennial of the Battle of Ayacucho in the areas of poetry and novels. Tiempos de la patria vieja. Novela histórica by Angélica Palma (Lima, 1878-1935) and Por la estirpe. Novela colonial by José Félix de la Puente (Trujillo, 1882-1959) were the winners. Paying attention to the narration of certain events, characters and especially the love plot, in this paper, I analyze the discursive representations of the independence process built by both novels after the first hundred years of the declaration of the Peruvian independence. I am interested in showing how, contrary to the official history, these novels give an account of the memory of the independence as a painful and torn civil war.